2021
DOI: 10.1055/s-0041-1730037
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of the Protein Z-Dependent Protease Inhibitor

Abstract: The protein Z (PZ)-dependent plasma protease inhibitor (ZPI) is a glycoprotein that inhibits factor XIa and, in the presence of PZ, FXa. Recently, ZPI has been shown to be an acute-phase protein (APP). As usually APPs downregulate the harmful effects of inflammation, we tested whether ZPI could modulate the increase of cytokines observed in inflammatory states. We observed that recombinant human ZPI (rhZPI) significantly decreases the levels of interleukin (IL)-1, IL-6, and tumor necrosis factor- α (TNF-α) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Noteworthily, two acute-phase reactants, CBG and ZPI, showed lower levels in patients in the COVID-19 studies. Both proteins play a role in reducing the harmful effects of inflammation [16,17]. The reduced plasma levels of CBG in COVID-19 patients have not been previously reported.…”
Section: Covid-19 Patients With Comorbidities Share a Common Plasma P...mentioning
confidence: 90%
See 1 more Smart Citation
“…Noteworthily, two acute-phase reactants, CBG and ZPI, showed lower levels in patients in the COVID-19 studies. Both proteins play a role in reducing the harmful effects of inflammation [16,17]. The reduced plasma levels of CBG in COVID-19 patients have not been previously reported.…”
Section: Covid-19 Patients With Comorbidities Share a Common Plasma P...mentioning
confidence: 90%
“…Similarly, the acute phase response protein ZPI was reduced in CPs compared to HCs. ZPI is increased in the acute phase response and promotes a reduction in the levels of inflammatory cytokines, such as interleukin (IL)-1, IL-6, and tumor necrosis factor-α (TNF-α) [16,45]. Recently, Toomer et al showed that ZPI is increased in moderate and severe COVID-19 patients compared to healthy controls by ELISA [46].…”
Section: Discussionmentioning
confidence: 99%
“…The ZPI/Z ratio can be used as a marker of inflammation because of the excess of production of ZPI in inflammation [ 14 ]. In our study, the ZPI/Z ratio was significantly increased in newborns of the recovered group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…An altered plasma PZ concentration is also associated with adverse pregnancy outcomes (miscarriage, stillbirth, intra uterine growth restriction and preeclampsia) [ 10 , 11 , 12 , 13 ]. Furthermore, ZPI has an anti-inflammatory role, and there is a major increase in the level of ZPI in response to inflammation [ 14 ]. As a result, an increased ratio of ZPI/Z suggests an inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Besides their anticoagulant effects, PROS1, SEPRINA10, and PROZ can also potentiate anti-inflammatory signaling. For instance, SER-PINA10 was recently identified to function as an acute phase protein [47] and subsequently shown to downregulate the expression of proinflammatory cytokines (TNFα, IL-1β, IL-6, and CCL3) independent of its anticoagulant effects [48], however, the underlying mechanism remain to be characterized. In line with these findings, low…”
Section: Introductionmentioning
confidence: 99%